Nilai-nilai dalam Proses Tradisi Lelocon Melalui adat Pernikahan di desa Lesung Batu Kabupaten Empat Lawang - Ego Putra Surya; Heryati Heryati; Dewi Setyawati (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This research aims to determine the values ​​in the process of the lelocon tradition through wedding customs in Lesung Batu village, Empat Lawang Regency. The social situation in this research is the traditional values ​​of jokes in wedding customs in Empat Lawang Regency. The location of this research is Lesung Batu Village, Empat Lawang Regency. Community groups living in Lesung Batu Village, Empat Lawang Regency are the subjects, and community attitudes or habits regarding wedding customs, which contain values, ​​are the activities studied. This research uses historical methods and qualitative research. The historical method has several stages: heuristics, source criticism, interpretation, and historiography. The data collection techniques used are documentation, interviews, and observation. The results of the research concluded that the value contained in the traditional wedding banter tradition of the people of Lesung Batu village, according to their ancestors' religious values, is that they believed in it so that they would be kept away from bad things that could disturb household life. The manifestation of values ​​in society is in the form of rewards, punishments, praise, and so on. Social values ​​are values ​​that are recognized as a result of consensus and closely related to views on the hope of shared prosperity in social life.